(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The term cyber security pertains to the protection of computer systems, networks, devices, data, and other related entities from potential threats, hazards, or assaults. The level of awareness of cyber security pertains to the extent to which a user possesses knowledge regarding the potential threats that may compromise the security of their network. In contemporary times, the utilization of social media platforms has witnessed a significant surge, thereby raising apprehensions regarding the safety of online activities and the perpetration of cyber offenses. The aforementioned circumstance necessitates the implementation of cyber security measures in conjunction with the cultivation of a positive digital social environment. Despite the convenience of accessing information from any location, there exists a potential risk of unauthorized disclosure of personal data to unintended recipients. Despite the prevalence of cybercrime as a significant threat to individuals, a considerable number of individuals remain unaware of its existence. Despite the fact that security is a subject that is addressed in distinct modules within numerous general computer science programs, it remains uncertain whether the implementation of cyber security measures is necessary. The objective of this research is to examine the correlation between the utilization of social media platforms and the level of consciousness regarding cybercrimes among individuals. The research employed the Apriori algorithm to detect associations, and the findings indicated robust associations among various variables pertaining to knowledge of cyber security. The statistical significance of the associations was evaluated through the utilization of three metrics, namely confidence, lift, and leverage. The results of the study could be utilized to enhance the knowledge of social media users regarding cyber security and emphasize the significance of staying up-to-date with cybercrimes and safeguarding oneself while utilizing social media platforms.